Rudy Frugtniet v ASIC: Things to consider if Victoria introduces a spent convictions regime (with 'A Message to You, Rudy'). (December 2019) - O'Toole, Suzanne; Keyzer, Patrick
The Legal and Social Issues Committee of the Victorian parliament will soon publish a report on spent convictions and criminal record discrimination. Victoria is the only state in Australia that does not have a spent convictions scheme. The purpose of this article is to review the recent decision of the High Court in Frugtniet v ASIC, a decision about the federal spent convictions scheme, and outline the lessons that decision provides for Victoria and for the successful appellant in that case.